Conceptualizing Student Housing Trough Trophic Design Around Universitas Sumatera Utara - Harisdani, Devin Defriza; Situmorang, Ira Sasmiadinata (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Universitas Sumatera Utara (USU) is a public university in Medan, North Sumatra. USU has many students from various cities. Most USU students come from out of town, so they need temporary residences in the form of student boarding houses. Several factors influence students’ choice of boarding houses, such as location, price, facilities, comfort, and building visuals. Good accessibility concerns the location of student boarding houses close to campus and several public facilities and shopping areas. Visual buildings are in the form of beauty that can be felt by residents and attract attention. In addition, to overcome the problem of high temperatures, some designs that are suitable for local tropical climates are needed. With these considerations in mind, applying the trophic design concept emerged as an appropriate solution. Through qualitative descriptive methods, surveys, and case studies, student housing was conceptualized and designed, incorporating the principles of trophic design. The hope is that this approach can offer a comprehensive solution, providing comfortable, relaxing, and aesthetically pleasing student housing for students.